EXPERT COMMUNITY AS A RESOURCE OF SCIENTIFIC SUPPORT FOR FOREIGN POLICY OF THE MODERN STATE (THE USA EXAMPLE) - Gennadiy Vladimirovich Kosov; Viktor Nikolaevich Panin; Maksim Alexandrovich Suchkov (Гуманитарные и юридические исследования)
The paper deals with the essence of “think tank” phenomenon. The authors offer their own definition and feature the characteristics of modern “think tanks”. Analysing the USA «think tanks» the authors reveal the mechanisms of functioning, influence and participation in foreign policy decision making in the modern state.